Normal glanular and meatal measurements in boys and men - ŞEKERCİ, ÇAĞRI AKIN; ÖZKAN, ONUR CAN; GENÇ, YUNUS EMRE; TANIDIR, YILÖREN; TARCAN, TUFAN; YÜCEL, SELÇUK (My University, 2023)
Objective: To determine the normal vertical urethral meatus length (ML), maximum glanular width (MGW), the glanular seam length (between the lowest edge of urethral meatus and the glans closure line corona) (GSL) and GSL/ML ratio in all age groups. Materials and Methods: Consecutive patients presented to urology and pediatric urology outpatient clinics were included in the study. Penile abnormalities, known endocrinological disorders, history of penile/urethral surgery were excluded. MGW, ML, and GSL were measured with a caliper. Glanular and meatal measurements were compared according to ages. Results: A total of 1398 boys and men (380 (27.18%) prepubertal (1-12), 203 (14.52%) adolescent (13-19), and 815 (58.30%) postpubertal (19-93)) with a median age of 31 years (range: 1-93) were included in the study. In consecutive age groups, ML and GSL gradually increased and became steady between 16-19 & 20-30 age groups and 10-12 & 13-15 age groups, respectively. On the other hand, MGW gradually increased until 20 years of age and became steady at median of 35 mm over 20 years of age. Another interesting finding was a rather stable GSL/ML ratio in all age groups. Pairwise comparison of different age groups seemed to be similar and suggests a fixed ratio of 1.33 (IQR: 0.6). Conclusion: The normal glanular and meatal measurements may guide the surgeons for better cosmetic results during hypospadias repair. The GSL/ML ratio appears to be a stable measure for all ages to achieve better cosmetic results.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; Üroloji; Urology